Experiential approaches to sustainability education: towards learning landscapes. Issue 1 (7th January 2019) - Backman, Malin; Pitt, Hannah; Marsden, Terry; Mehmood, Abid; Mathijs, Erik
Abstract : Purpose: This paper aims to critically reflect the current specialist discourse on experiential approaches to higher education for sustainable development (HESD). Limitations to the current discourse are identified, and as a result, an alternative approach to the study of experiential education (EE) within HESD is suggested. Design/methodology/approach: Three research questions are addressed by analysing the literature on EE and experiential learning (EL) within HESD in specialist academic journals. Findings: There is a consensus among authors regarding the appropriateness of experiential approaches to HESD. However, limitations to the current discourse suggest the need for an alternative approach to studying EE within HESD. Therefore, this paper proposes the application of the learning landscape metaphor to take a more student-centred and holistic perspective. Originality/value: The learning landscape metaphor has previously not been applied to EE within HESD. This alternative conceptualisation foregrounds student perspectives to experiential initiatives within HESD. The holistic approach aims to understand the myriad influences on students learning, while allowing examination of how experiential approaches relate to other educational approaches within HESD.